SISTEM AKUNTANSI PEMBELIAN BAHAN BAKU PADA PT. XYZ - Minggu, Minggu; Mardiana, Diand; Erlangga, Wiliam Eri; Evalina, Evalina (JURNAL LENTERA AKUNTANSI, 2023)
The culinary industry represents one of the most dynamic and continuously growing sectors in response to the increasing demand for ready-to-eat and instant food products. This study aims to analyse the accounting system for raw material purchases at PT. XYZ. Specifically, it seeks to: (1) identify the documents and records employed in the purchasing system, (2) examine the departments involved in the process, and (3) analyse the accounting procedures related to raw material procurement. The research adopts a qualitative descriptive approach, utilizing data collection methods such as observation, in-depth interviews, and a review of relevant literature. The findings reveal that the raw material purchasing accounting system at PT. XYZ comprises several implementation procedures and standardized flowcharts. The system incorporates a variety of documents and records to ensure accurate tracking and accountability. Furthermore, multiple organizational units are involved in the process, each carrying out specific roles and responsibilities. It is evident that the accounting system has been implemented in alignment with the company’s Standard Operating Procedures (SOPs). The documentation and record-keeping practices are sufficient to meet the demands of transaction recording and verification. Each department involved in the purchasing process demonstrates a clear understanding of its duties, contributing to the effectiveness and reliability of the overall system. Additionally, the procedures for recording raw material purchases adhere strictly to the SOPs established by the company, ensuring both compliance and operational efficiency